Analysis of a sensor for fruit classification using Rician k-factor in a continuous process - Leekul, P.; Krairiksh, M. (My University, 2017)
This paper presents simulation results that describes feature of a sensor system in a continuous process. The Rician k-factors from a single frequency-monostatic and a wideband-bistatic measurements can be used as indicators for classifying maturity stage of durian fruits.
Keywords: bi-static; continuous process; microwave sensor; Monostatic; Rician k-factor